Testosterone deficiency syndrom – diagnosis and treatment - Hanecki, Ryszard (Menopause Review/Przegląd Menopauzalny, 2008)
Androgen deficiency in the ageing male has become a topic of increasing interest and debate throughout the world. Demographic data demonstrates the increasing percentage of the population that is found in the older age groups. The data also support the concept that testosterone falls progressively with age and that a significant percentage of men over the age of 60 years have serum testosterone levels that are below the lower limits of young adult men (age 20-30 years). The past decade has brought evidence of benefit of androgen treatment of hypogonadal men on multiple target organs and recent studies show short-term beneficial effects of testosterone in older men that are similar to those in younger men.